Bibliometric Analysis of Studies on the Artificial Intelligence in Science Education with VOSviewer - Hayriye Nevin Genc; Nuriye Kocak (Journal of Education in Science, Environment and Health)
Understanding the trends and developments in artificial intelligence research in science education, which has rapidly advanced in recent years, is crucial for technological innovations and applications in education. Therefore, this study examines research on artificial intelligence in science education conducted between 2019 and 2023 (the last five years) through bibliometric analysis, utilizing the Web of Science database. VOSviewer was used for the analysis. As a result of scanning the Web of Science database under these criteria, 867 studies were identified. Analyzing the distribution of these 867 publications by year reveals a concentration in 2023 and 2022. In terms of publication distribution by country, the leading contributors were the USA, China and Australia. The most prolific authors were identified as D. Gasevic, Z. Xiaoming and S. S. Oyelere. Regarding the number of documents and citations in journals, "Computers & Education" ranked first. The most cited used keywords were "Machine Learning" and "Artificial Intelligence", followed by "Learning Analytics", "Data Science" and "Higher Education". The findings illuminate recent research on artificial intelligence in science education. This study is expected to assist researchers in identifying trends within the field and to provide guidance for future studies.